PFOA Cooperative Adsorption to DPPC Monolayers and Ordering of Interfacial Water - Sobolewski, Tess N.; Walker, Robert A. (The journal of physical chemistry. B, 2025)
Vibrational sum frequency generation (VSFG) and Langmuir trough surface pressure measurements were used to investigate how the soluble surfactant perfluorooctanoic acid (PFOA) affects dipalmitoylphosphatidylcholine (DPPC) monolayers adsorbed to the air–water interface. Studies were performed as a function of PFOA concentration for DPPC surface coverages of 40 Å2/monomer and 55 Å2/monomer, corresponding to tightly packed and moderately packed monolayers, respectively. VSFG data showed that PFOA does not affect the structure of tightly packed DPPC monolayers, but cooperative adsorption of PFOA to moderately packed DPPC monolayers forces lipid compression, creating highly ordered acyl chains. PFOA adsorption to moderately packed DPPC monolayers also creates a charged interface, evidenced by significant intensity growth in the –OH stretching region as interfacial water is oriented by the resulting electric double layer. Interestingly, this effect is also observed for the tightly packed DPPC monolayers, implying that the surfactant adsorbs to the solvated lipid headgroups without affecting lipid chain conformation. PFOA–DPPC interactions at all DPPC surface coverages are apparent in Langmuir isotherms, where PFOA concentrations as low as 10 μM induce DPPC monolayer liftoff at 130 Å2/monomer rather than ∼90 Å2/monomer observed in the absence of PFOA and a monolayer collapse pressure that is ∼6 mN/m lower than that for a pure DPPC monolayer.